Proust and the squid : the story and science of the reading brain - Wolf, Maryanne (Harper Perennial, 2008)
A developmental psychologist evaluates the ways in which reading and writing have transformed the human brain, in an anecdotal study that reveals the significant changes in evolutionary brain physiology throughout history.